Dietary antioxidant supplementation combined with Quercetin improves cycling time trial performance - MacRae, H. S.-H.; Mefferd, K. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
We investigated whether 6 wk of antioxidant supplementation (AS) would enhance 30 km time trial (TT) cycling performance. Eleven elite male cyclists completed a randomized, double-blind, cross-over study to test the effects of twice daily AS containing essential vitamins plus quercetin (FRS), and AS minus quercetin (FRS-Q) versus a baseline TT (B). MANOVA analysis showed that time to complete the 30 km TT was improved by 3.1% on FRS compared to B (P = 0.01), and by 2% over the last 5 km (P = 0.05). Absolute and relative (%HRmax) heart rates and percent VO2max were not different between trials, but average and relative power (% peak power) was higher on FRS (P = 0.01). Rates of carbohydrate and fat oxidation were not different between trials. Thus, FRS supplementation significantly improved high-intensity cycling TT performance through enhancement of power output. Further study is needed to determine the potential mechanism(s) of the antioxidant efficacy.